Deciphering Urban Happiness: Analysis of Machine Learning Approaches for Comprehensive Urban Planning - Airlangga, Gregorius (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
This study embarks on an analytical journey to decode the complexities of urban happiness, leveraging a suite of advanced machine learning models. At the heart of our methodology is the innovative application of CatBoost, Random Forest, Gradient Boosting, and Linear Regression models, each chosen for its distinct ability to navigate the multifaceted nature of our urban dataset. CatBoost is highlighted for its proficiency in managing categorical data, essential in reflecting the diverse elements of urban environments. Concurrently, Random Forest's capability in reducing variance and overfitting, along with Gradient Boosting's precision in optimizing across various loss functions, plays a pivotal role in the accuracy of our predictions. Linear Regression serves as a baseline, offering simplicity and interpretability for comparative analysis. Central to our evaluation is the Root Mean Squared Error (RMSE) metric, providing a quantitative measure of our models' accuracy. This approach is instrumental in translating the intricate relationships within urban data into actionable insights for urban planning and policy-making. Our study not only demonstrates the effectiveness of an ensemble approach in machine learning but also emphasizes the importance of interpretability in model selection and evaluation. The findings offer a comprehensive understanding of urban happiness, serving as a valuable resource for stakeholders in urban development and policy formulation. This research marks a significant stride in harnessing machine learning's potential to enrich urban life quality.